Effectiveness of Learning Media With Flip PDF Application in Improving Economic Learning Outcomes (Journal of Economic Education, 2022)
Flip PDF is an audio-visual learning media that can be developed and accessed in the form of e-modules on most Android smartphones. Until now, teachers at SMA 1 Weleri Kendal in Central Java have not used technology as a medium or source of learning. Because the teacher's learning approach has fewer variations, it has an impact on student learning outcomes, which is not optimal, and they have never used learning media using interactive software such as Flip PDF. This research with the Research and Development method is based on J. Sweller's E-Learning Theory, which is a learning media theory that explains cognitive science principles in multimedia learning. The method of research and development used to create certain products, as well as the Borg and Gall Modification Model used to test the product's effectiveness and impact. Product validation and testing, Mann Whitney differential test, Normalized N-Gain, and Practicality Average were used to analyze the data. According to the findings of the study, the developed E-module with Flip PDF is valid and appropriate for use by validators, material experts, media, and students. The Mann Whitney test results show that there are significant differences in the students' pre-test and post-test after using Flip PDF in the learning process. On average, media and material experts consider Flip PDF e-module to be very practical and simple to use. Furthermore, students of SMAN 1 Weleri found the Flip PDF E-module to be very useful. E-modules are thought to be simple to use anywhere and at any time. The N-Gain test indicates that students who use e-modules with PDF flips improve their economic learning outcomes in a good way. The results of the field test show that it operates very well. Students discover that an e-module with a flip PDF is simple to use with a smartphone/notebook/computer because it can also be accessed online.